Using novel Lactobacillus plantarum to produce lactic acid from lignocellulosic biomass in an integrated simultaneous saccharification and fermentation process - Tu, Wei-Lin; Hsu, Teng-Chieh; Wang, Chun-An; Guo, Gia-Luen; Chao, Yu (Bioresources, 2019)
The isolated bacterium Lactobacillus plantarum is strongly tolerant of lignocellulose-derived inhibitory compounds and possesses the ability to produce lactic acid in the presence of 8.0 g/L furfural, 6.0 g/L hydroxymethylfurfural, 4.0 g/L vanillin, and 4.0 g/L syringaldehyde. This bacterium was used in an integrated simultaneous saccharification and fermentation (SSF) process for the production of lactic acid using whole rice straw slurry (with a high solids content of 17%) that had been pretreated with dilute sulfuric acid. This method achieved a lactic acid concentration of 65.6 g/L, which corresponded to a cellulose-to-lactic acid conversion yield of 69%. These results demonstrated that isolated bacterium and the proposed integrated SSF process are able to produce high concentrations of lactic acid. Furthermore, this proposed process does not require detoxification and had a conversion efficiency that is comparable to that obtained using the conventional SSF process, which requires the addition of fresh water. Therefore, it was concluded that the proposed process is promising for commercial lactic acid production and could make the production of lactic acid from lignocellulosic biomass more practical in the future.